SOLUSI ADAPTASI KEBIASAN BARU DENGAN KREATIVITAS DAN INOVASI - Acuh Dharmawan Junaidi (Journal of Management and Business, 2022)
During the pandemic experienced by the Indonesian people, they are required to live with a new life order, which can make peace with Covid 19. The purpose of this descriptive research is to find out the concepts of creativity and innovation that must be developed in adapting to new habits in the covid 19 pandemic. Research This study uses a library research approach. The result is that innovation can be said to be a product of society's adaptation to changes or unpleasant conditions. When in a situation of urgency or threat, individuals will try to do something that can help them get out of problems, and creativity has a very big role in this..